The Value of Laparoscopic Simultaneous Colorectal and Hepatic Resection for Synchronous Colorectal Cancer Liver Metastasis: A Propensity Score Matching Study - Zhou, Jiamin; Feng, Longhai; Li, Xinxiang; Wang, Miao; Zhao, Yiming; Zhang, Ning; Wang, Longrong; Zhang, Ti; Mao, Anrong; Xu, Ye; Wang, Lu (Frontiers in Oncology, 2022)
Purpose The aim of this study is to investigate the value of total laparoscopic simultaneous colorectal and hepatic resection in patients with synchronous colorectal cancer liver metastases (sCRLMs). Methods sCRLM patients who underwent simultaneous resection from December 2014 to December 2018 in Shanghai Cancer Center, Fudan University were recruited and analyzed retrospectively. The patients were divided into laparoscopic, open, and hybrid surgery groups. The intraoperative information, postoperative short-term outcome, and long-term survival were compared among the three groups. Propensity score matching (PSM) was performed to balance baselines. Results A total of 281 patients were recruited. After PSM, 34 patients were selected from both the laparoscopic and the open surgery group. Forty-seven patients were also selected from both the laparoscopic and the hybrid surgery group. The clinicopathologic baselines between the laparoscopic surgery group and the other two groups were well matched. All the operation-related indicators between laparoscopic surgery and hybrid surgery were similar. However, compared with open surgery, laparoscopic surgery showed significantly longer operation time (229.09 ± 10.94 min vs. 192.24 ± 9.49 min, p = 0.013) and less intraoperative blood loss [100.00 (50.00–300.00) ml vs. 200.00 (150.00–400.00) ml, p = 0.021]. For postoperative morbidity, there was no significant difference between the laparoscopic surgery group and the hybrid or the open surgery group (23.40% vs. 31.91% and 17.65% vs. 26.47%, p = 0.356 and p = 0.380). Long-term survival analysis showed that there were no significant differences in all 1-, 3-, and 5-year overall survival, liver recurrence-free survival (RFS), and whole RFS between laparoscopic surgery and hybrid surgery (p = 0.334, p = 0.286, and p = 0.558) or open surgery (p = 0.230, p = 0.348, and p = 0.450). Conclusions Laparoscopic simultaneous resection for sCRLM shows slight advantages in surgical safety and short-term outcome, and does not compromise long-term survival.